Asymmetry of lateral abdominal wall muscles in static and dynamic conditions: A preliminary study of professional basketball players - Adamczyk, W.; Bialy, M.; Stranc, T. (Science & Sports, 2016)
Objectives: To establish right/left asymmetry in the lateral abdominal wall muscle group (LAM) and to determine whether this asymmetry is dependent on the motor task type (static/dynamic). Summary of facts and results: This was a cross-sectional study of ten men who had been playing basketball professionally for a minimum of 10 years. Asymmetry in the thickness of all the lateral abdominal wall muscles - transversus abdominis, internal oblique and external oblique - and with total LAM thickness were calculated. Thickness data were collected with M-mode ultrasound imaging during two conditions: static (in a static upright position) and dynamic (during rapid contralateral arm abduction). Thickness asymmetry of each muscle and the total LAM thickness was above 9% (P < 0.01) and was independent of the type of motor task (P > 0.05). Conclusion: LAM asymmetry in a group of basketball players is a stable and independent factor regardless of whether the motor task is static or dynamic.